Multi-objective optimization of kitchen comfort based on arithmetic superposition index P - Shunyu Zhang; Xiangrui Zhao; Liangguo Cheng; Zhihang Shen; Zhenlei Chen (Case Studies in Thermal Engineering)
For the accumulation of pollutants and high-temperature environment in the kitchen, this paper comprehensively considers kitchen pollution emissions, air supply, and thermal comfort, innovatively introduces the concepts of arithmetic superposition index P and human respiratory zone thermal sensitivity weighting, and proposes a multi-objective optimization of kitchen comfort based on the P index. This study adopts a combination of orthogonal experiments and computational fluid dynamics (CFD) simulations to study the exhaust characteristics of range hoods under different structural parameters and compares and analyzes the rationality and effectiveness of different auxiliary ventilation methods in kitchen ventilation systems to propose the optimal solution. The research findings indicate that adjusting the range hood barrier angle significantly reduces kitchen pollution, and workstation air supply markedly improves kitchen and breathing zone comfort. Optimizing range hood parameters (178°angle, 1.544m height, 20.57 Pa pressure) increased PM10 capture efficiency by 25.68 % and reduced PM10 intake fraction by 72.55 %. This also decreased the breathing zone's weighted PMV by 37.17 % and increased kitchen ADPI by 27.7 %. Compared to no auxiliary air supply, workstation air supply decreased kitchen PMV by 53.08 % and breathing zone thermal weighted PMV by 96.99 %. Additionally, it lowered the thermal weighted air age in the breathing zone by 11.98 % and improved ventilation efficiency by 12.55 %, greatly enhancing kitchen comfort.